Permskaâ naučnaâ škola funkcionalʹnoj stilistiki - Štajn, Klara È. (Stylistyka, 2021)
Соттишсайуе stylistics is а rew f^ld of modem funct^^l stylistics and it is formed оп Ле basis of о^ег sciences, which study text as а fomi of соттитсайоп and pheno- тепоп of idtostyfa. In tontrast to linguistics of text and linguistic poetics соттишсайуе stylistics studies text in ^ре^ to author and addressee’s activity. Unlike pragmatics, psycholinguistics, psychopoetics, which аге guided by ^е theory of speech activities, ram- municative stylistics concems linguistic-stylistic aspects of intercourse speech in ^еіг textual realization. And аt Ле same time а research of structural and semantic text о^ат- zatwn in the view of communicative effect is considered ая analysis caused by some factors such as stylistic usage and author’s idiostyle. Activities арргоа^ in the context of communicative stylistics is connected with its examination as а fact оПтНа! communicative author’s activity and an оЬ|е^ of secondary communicative reader’s activity. 1Ъе аіт of communicative stylistics is to work up the problems of efficacy of author and addressee’s textual activity taking into account specific character of language рє^оп, f^ld of intercourse, аіт and tasks, genre and style peculiarities of text. In accord with а^^о- pocentric approach to text idiostyle is considered as а dominant notion and it gets another communicative sense. This notion contains multifold demonstration of author’s language person in the structure, semantics and pragmatics of text. The questions of normalization in text activity are considered as the main problem of communicative stylistics. A new aspect of this problem is that it is connected with efficacy intercourse of author and reader. Taking into consideration bilateral character of communication (initial and secondary communicative activity which is connected with text formation and text perception and interpretation) textual norm is regarded as an important factor for dialogic intercourse of author and addressee, which shows a standard of textual activity for a certain sphere of communication. Textual nom1 is defined as follows: 1) it is firm rules of textual activity which are prevalent historically and accepted by a society; standard texts for a certain sphere of communication are fomied on the basis of these rules; 2) it is a system of communicative-pragmatic, genre and style, composition and speech norms, which is proper for a certain type of text and it shows its communicative essence, linguistic character and extralinguistic orientation; 3) it is a harmonious organization of all structural elements of text in accord with the basic idea of author and direction of attention toward addressee. This notion of textual norm takes into account a complex of the f ollowing f actors: 1) place of text in the structure of universal model of speech communication by Roman O. Ja- kobson; 2) levels of model oflanguage person which is out of text according to the theory of Yurij N. Karaulov; 3) communicative characteristics of speech which text must meet the requirements; 4) the main features and characteristics of text.ln spite of their stability textual nomis are historically changed and varied depending on the type oftext (mainly it depends on its genre and style peculiarities, sphere of communication, literary school which author follows) and author’s intention and addressee’s factor.